“ DISASTER IS HANGING OVER OUR MASTER AND HIS WHOLE HOUSEHOLD…”(1 SAM. 25:17): CONTEXTUALIZING ABIGAIL’S ROLE IN THE QUEST FOR PEACE IN NIGERIA - Abigail, Tanu; Kate, Jibromah, O. (European Scientific Journal, ESJ, 2015)
Most times, it seems peace keeping mission is perpetually the prerogative function of the government and as such individuals and communities exonerate themselves and allow unguided utterances and mindsets ruin the land. In the traditional setting of the pre-colonial period traditional means were used to restore peace in homes and in tribal conflicts. In the Nigerian society today, talks and proposals are on, in favour or against community policing because the traditional system of securing the life and property of the people is broken down and is now rested on the executive arm of government. But we are told in the Hebrew Bible of Abigail who single-handedly assuage the anger of David and stopped the shedding of innocent blood. Within this context we have looked at issues in some trouble rocked communities in Nigeria and have discovered that, the best method of cleaving to peace is through dialogue, using the Abigail’s strategy of peacemaking as an exemplar. This study will use the inculturation approach to bring to bare peace in the society.